**Taylor series** is an example of infinite series derived from the expansion of `f(x)` about a single point. It is represented by infinite sum of `f^n(x)` centered at `x=c` . The **general formula for Taylor series** is:

`f(x) = sum_(n=0)^oo (f^n(c))/(n!) (x-c)^n`

or

`f(x) =f(c)+f'(c)(x-c) +(f^2(c))/(2!)(x-c)^2 +(f^3(c))/(3!)(x-c)^3 +(f^4(c))/(4!)(x-c)^4 +...`

To...

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

**Taylor series** is an example of infinite series derived from the expansion of `f(x)` about a single point. It is represented by infinite sum of `f^n(x)` centered at `x=c` . The **general formula for Taylor series** is:

`f(x) = sum_(n=0)^oo (f^n(c))/(n!) (x-c)^n`

or

`f(x) =f(c)+f'(c)(x-c) +(f^2(c))/(2!)(x-c)^2 +(f^3(c))/(3!)(x-c)^3 +(f^4(c))/(4!)(x-c)^4 +...`

To determine the Taylor polynomial of degree `n=4 ` from the given function `f(x)=1/x^2` centered at `c=2` , we may apply the definition of Taylor series.

For the list of `f^n(x)` up to `n=4` , we may apply Law of Exponent: `1/x^n = x^-n` and Power rule for derivative: `d/(dx) x^n= n *x^(n-1)` .

`f(x) = 1/x^2 or x^(-2)`

`f'(x) = d/(dx)x^(-2)`

`=-2 *x^(-2-1)`

`=-2x^(-3) or -2/x^3`

`f^2(x)= d/(dx) -2x^(-3)`

`=-2 *d/(dx) x^(-3)`

`=-2 *(-3x^(-3-1))`

`=6x^(-4) or 6/x^4`

`f^3(x)= d/(dx) 6x^(-4)`

`=6 *d/(dx) x^(-4)`

`=6 *(-4x^(-4-1))`

` =-24x^(-5) or -24/x^5`

`f^4(x)= d/(dx) -24x^(-5)`

` =-24 *d/(dx) x^(-5)`

`=-24 *(-5x^(-5-1))`

`=120x^(-6) or 120/x^6`

Plug-in `x=2` , we get:

`f(2)=1/2^2 =1/4`

`f'(2)=-2/2^3 = -1/4`

`f^2(2)=6/2^4 =3/8`

`f^3(2)=-24/2^5 = -3/4`

`f^4(2)=120/2^6= 15/8`

Applying the formula for Taylor series, we get:

`sum_(n=0)^4 (f^n(2))/(n!) (x-2)^n`

`=f(2)+f'(2)(x-2) +(f^2(2))/(2!)(x-2)^2 +(f^3(2))/(3!)(x-2)^3+(f^4(2))/(4!)(x-2)^4`

`=1/4+(-1/4)(x-2) +(3/8)/(2!)(x-2)^2 +(-3/4)/(3!)(x-2)^3+(15/8)/(4!)(x-2)^4`

`=1/4-1/4(x-2) +(3/8)/2(x-2)^2 -(3/4)/6(x-2)^3+(15/8)/24(x-2)^4`

`=1/4-1/4(x-2) + 3/16(x-2)^2 -1/8(x-2)^3+5/64(x-2)^4`

The **Taylor polynomial** of degree `n=4` for the given function `f(x)=1/x^2 ` centered at `c=2` will be:

`P_4(x)=1/4-1/4(x-2) + 3/16(x-2)^2 -1/8(x-2)^3+5/64(x-2)^4`